Quantum chemical studies on some new bipyrazole derivatives as corrosion inhibitors for steel materials. Issue 3 (3rd May 2016) - Ju, Hong; Chen, Jiejing; Sun, Can; Li, Yan
Abstract : Purpose: The purpose of this study is to perform quantum chemical calculations based on the DFT method on four bipyrazoles used as corrosion inhibitors for the plain carbon ("mild") steel in acid media to determine the relationship between inhibition efficiency and the molecular structure of inhibitors. Design/methodology/approach: Several quantum chemical parameters, such as the charge distribution, energy and distribution of highest occupied molecular orbital and lowest unoccupied molecular orbital, the absolute electronegativity (χ) values and the fraction of electrons (△N) transferring from inhibitors to the steel surface, were calculated and correlated with inhibition efficiencies. Findings: The results showed that the inhibition efficiency of bipyrazole increased with the increasing in EHOMO, and the areas containing N atoms were the most probable sites to donate electrons for adsorbing the inhibitor molecules onto the metal surface. Originality/value: It is a useful method to investigate the mechanisms of reaction by calculating the structure and electronic parameters, which can be obtained by means of theoretical quantum theory. Thus, the behavior and mechanism of the organic inhibitors can be obtained. Quantum chemical method can also be used to guide the selection and molecular design of inhibitors.